(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
Social Networking is one of the most promising technologies that can be used for e-learning purposes to create an interactive learning environment and support student learning. However, its uses for educational purposes are still in the early stages and the potential advantages and beneï¬ts of social networking in education are still very much underappreciated and undervalued. The purpose of this article is to discuss the potential advantages of web 2.0 technologies and tools in particular Social Networking Sites (SNS) to support students engagement and student learning. Moreover, the paper highlights the main problems associated with e-learning systems and summarizes the advantages and disadvantages of the Learning Management System (LMS) and Social Media. In addition, this paper presents a review of the most popular social media tools that can be integrated in e-learning systems towards the Personal Learning Environment and lifelong learning.